2022
DOI: 10.1186/s40168-022-01227-w
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus murinus alleviate intestinal ischemia/reperfusion injury through promoting the release of interleukin-10 from M2 macrophages via Toll-like receptor 2 signaling

Abstract: Background Intestinal ischemia/reperfusion (I/R) injury has high morbidity and mortality rates. Gut microbiota is a potential key factor affecting intestinal I/R injury. Populations exhibit different sensitivities to intestinal I/R injury; however, whether this interpopulation difference is related to variation in gut microbiota is unclear. Here, to elucidate the interaction between the gut microbiome and intestinal I/R injury, we performed 16S DNA sequencing on the preoperative feces of C57BL/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 100 publications
6
81
0
Order By: Relevance
“… Kaushal and Kansal (2014) demonstrated that L. acidophilus and B. bifidum increased the phagocytic potential of aged mouse macrophages to improve immunity. A recent probiotic study showed that L. rhamnosus can reduce intestinal ischemia–reperfusion injury in mice by activating IL-10 release from macrophages through the TLR2 receptor signaling pathway ( Hu et al, 2022 ).…”
Section: Intestinal Immune Barriermentioning
confidence: 99%
“… Kaushal and Kansal (2014) demonstrated that L. acidophilus and B. bifidum increased the phagocytic potential of aged mouse macrophages to improve immunity. A recent probiotic study showed that L. rhamnosus can reduce intestinal ischemia–reperfusion injury in mice by activating IL-10 release from macrophages through the TLR2 receptor signaling pathway ( Hu et al, 2022 ).…”
Section: Intestinal Immune Barriermentioning
confidence: 99%
“…Hu et al found that differences in the pre-II/R gut microbiota, especially in the abundance of Lactobacillus murinus , strongly influence II/R susceptibility and outcome. Moreover, the abundance of Lactobacillus murinus in preoperative feces of cardiopulmonary bypass patients was significantly negatively correlated with postoperative intestinal injury ( Hu et al., 2022 ). Pretreatment of animals with Bifidobacteria prevented II/R-induced bacterial translocation, reduced proinflammatory cytokine release, endotoxin levels, intestinal epithelial apoptosis, disruption of tight junctions, and increased SCFA concentrations, leading to recovery microbiota and mucosal integrity ( Wang et al., 2013b ).…”
Section: The Effect Of Gut Microbiota On Ii/rmentioning
confidence: 99%
“…Hu et al showed that Lactobacillus murinus attenuates II/R injury in mice via macrophages. In addition to intestinal bacterial strains, it has recently been found that intestinal flora metabolites are also non-negligible substances in II/R ( Hu et al., 2022 ). Deng et al al.…”
Section: The Effect Of Gut Microbiota On Ii/rmentioning
confidence: 99%
“…Lactobacillus murinus relieves intestinal I/R injury by activating TLR2 signal and promotes the release of Interleukin-10 (IL-10) from M2 macrophages, which can significantly prevent intestinal I/R injury. In addition, correlation analysis showed that clinically, the abundance of Lactobacillus murinus in the feces of patients undergoing cardiopulmonary bypass surgery is closely related to the degree of postoperative intestinal I/R injury [67]. The combined use of L. plantarum DSM 9843 and rose hip reduces cecal I/R injury, the oxidative stress level of cecal tissue and the abundance of enterobacter [68].…”
Section: Intestinal Bacteriamentioning
confidence: 99%
“…Intestinal ischemia/reperfusion (I/R) injury is common in the perioperative period, especially in both surgical and trauma patients, and has high morbidity and mortality associated with it [1][2][3]. Intestinal I/R plays an important role in the pathophysiological evolution of severe infection, trauma, shock, intestinal obstruction, mesenteric artery embolism, abdominal aortic aneurysm surgery, cardiopulmonary bypass surgery, liver transplantation, and small intestine transplantation [4,5].…”
Section: Introductionmentioning
confidence: 99%